High ammonium recycling in an anthropogenically altered Yeongsan River Estuary, South Korea - Lee, Jiyoung; An, Soonmo (Frontiers in Marine Science, 2022)
Regenerated nitrogen (N) cycling was studied in a turbid and nutrient-rich estuary located in the southeast region of the Yellow Sea (Yeongsan River Estuary; YRE), in order to elucidate the biogeochemical consequences of coastal development. Ammonium regeneration and potential uptake rates were measured from March 2012 to June 2013 using 15N tracer techniques. Size fractionation suggested that small-sized bacteria (<0.7 μm), rather than zooplankton, were responsible for most of the ammonium regeneration. Intermittent freshwater discharge events might have prevented stable zooplankton community development and caused the insignificant role of zooplankton in ammonium regeneration. Ammonium regeneration and potential uptake rates were relatively high (0.1–1.2 and 0.2–1.5 µmol L−1 h−1, respectively), and were highest during summer. Ammonium turnover times were shorter than water residence times throughout the study period. These results indicate that ammonium is actively recycled and is likely to supply enough N required to sustain the high primary productivity observed in the YRE (50%–450%). Reduced turbidity and increased water residence times caused by the construction of an estuarine dam in the YRE have probably resulted in the formation of optimal conditions for the high ammonium regeneration.